A decade of genomic and phenotypic adaptation of carbapenem-resistant Acinetobacter baumannii - Astri D. Tagueha; Cartesio D’Agostini; Cartesio D’Agostini; Daniela Scribano; Carlotta Fiorilla; Dolores Limongi; Dolores Limongi; Silvia Fillo; Luca Corrent; Martina Lipari; Florigio Lista; Lucia Nencioni; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionAcinetobacter baumannii exhibits high genomic plasticity, enabling it to acquire virulence factors and antibiotic resistance (AR). Understanding its evolutionary adaptations is crucial for developing effective therapeutic strategies.MethodsThirty clinical isolates collected from two distinct time periods, defined as older (2010–2013), and recent (2022–2023),- were compared phenotypically (antibiotic resistance, growth, biofilm formation, desiccation tolerance, invasiveness) and genotypically (whole-genome sequencing).ResultsAll isolates displayed an extensively drug-resistant phenotype. Overall, respiratory isolates harbored a higher content of antibiotic-resistant genes (ARGs), with older isolates showing 12.5% increases in the average number of ARGs compared to recent urine isolates (P = 0.02). More than 50% of the strains with faster growth, stronger biofilm formation, and increased lung cell invasiveness were recent respiratory isolates, while over 70% of older isolates showed greater desiccation tolerance and bladder cell invasiveness. Eleven virulence factor genes were shared between old and recent respiratory isolates, and eight were common between recent urinary and respiratory strains with no overlap among urinary isolates. Statistically significant positive correlations were observed between fast-growing and strong biofilm-forming respiratory isolates as well as their lung cell invasiveness. Conversely, negative correlations were found between collection time, isolation site, and host cell invasiveness. Analysis of macrocolony types revealed no link to phenotypic behavior.ConclusionSignificant genetic variability was found between past and recent isolates. Older isolates had more genes involved in adhesion and nutrient uptake, while recent respiratory strains demonstrated increased biofilm formation and invasiveness, reflecting adaptation to clinical pressures. These findings highlight the dynamic evolution of A. baumannii, providing insights for future therapeutic strategies and infection control.